2016
DOI: 10.1016/j.neuroimage.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Tracking neural correlates of successful learning over repeated sequence observations

Abstract: The neural correlates of memory formation in humans have long been investigated by exposing subjects to diverse material and comparing responses to items later remembered to those forgotten. Tasks requiring memorization of sensory sequences afford unique possibilities for linking neural memorization processes to behavior, because, rather than comparing across different items of varying content, each individual item can be examined across the successive learning states of being initially unknown, newly learned,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 113 publications
1
34
0
Order By: Relevance
“…The second paradigm involves the learning of simple sequences 6 . The third emulates a standard neuropsychological processing speed task, which involves multiple perceptual decisions, short-term memory, and motor responses.…”
Section: Background and Summarymentioning
confidence: 99%
“…The second paradigm involves the learning of simple sequences 6 . The third emulates a standard neuropsychological processing speed task, which involves multiple perceptual decisions, short-term memory, and motor responses.…”
Section: Background and Summarymentioning
confidence: 99%
“…The simplest paradigm permits the tracing of the three major processing stages for simple contrast decisions (O'Connell et al, 2012). The second paradigm involves the learning of simple sequences (Steinemann et al, 2016). The third emulates a standard neuropsychological processing speed task, which involves multiple perceptual decisions, short-term memory, and motor responses.…”
Section: Background and Summarymentioning
confidence: 99%
“…In order to evaluate the neural correlates of declarative learning, we included an explicit visual sequence learning paradigm, in which subjects repeatedly view a fixed sequence of flashed visual locations and attempt to memorize it in order to make regular intermediate recall reports. This task was originally developed by Moisello, Ghilardi and colleagues as a control condition for the examination of spectral EEG signatures of visuo-motor learning (Moisello et al, 2013), and was recently shown to be highly informative in its own right, in providing reliable indices of memory formation and surprise-modulated stimulus processing that related systematically to the ongoing progress of learning (Steinemann et al, 2016). An important aspect of the paradigm is that the information to be remembered (flashed location) is of the most elementary kind and computed very rapidly in the brain, so that perceptual decisions regarding the immediately presented item are completed quickly, allowing the longer-lasting neural signatures of memory formation to be reliably distinguished from the short-lived processes of immediate stimulus identification.…”
Section: Paradigm #5 (Active): Sequence Learningmentioning
confidence: 99%
See 2 more Smart Citations